Evaluasi Dana Desa dan Alokasi Dana Desa Pada Desa Bantan Tengah Tahun Anggaran 2019 - Nana, Devita Mardalena; Suharyono (Akuntansi dan Manajemen, 2020)
This research consign to knowing evaluation of village funds and allocation of village funds to the village of Bantan Tengah for the 2019 fiscal year (case study in the village of Central Bantan). The type of research that use in this case as deskriptif kualitatif. The results of this research is showing that the use of village funds and the allocation of village funds in the middle of bantan village have not been used to the fullest, because there are still a number of unrealized. Unrealized funds from village funds are Rp. 113,775,041, -, 9.58% of the total budget, while funds from the allocation of village funds amounted to Rp. 717,334,285, - 32.73% of the total budget. Activities programs, while the unrealized activities are management of villageowned libraries, construction / rehabilitation / improvement of road infrastructure, social training / extension / about the environment, strengthening and increasing the capacity of security personnel, port maintenance, construction / rehabilitation / upgrading of buildings / infrastructure, developing village information systems, organizing PAUD / TK / TPA / TKA / TPQ / Madrasah, maintenance of residential neighborhood / alley roads, maintenance of facilities cultural infrastructure, youth development / youth / sports clubs, disaster management activities, the most dominant program that is not realized, namely the infrastructure development.